Demand or supply? An empirical exploration of the effects of climate change on the macroeconomy - Matteo Ciccarelli; Fulvia Marotta (Queen Mary University of London, School of Economics and Finance, 2021)
Using a panel of 24 OECD countries for the sample 1990-2019 and a standard macroeconomic framework, the paper tests the combined macroeconomic effects of climate change, environmental policies and technology. Overall, we find evidence of significant macroeconomic effects over the business cycle: physical risks act as negative demand shocks while transition risks as downward supply movements. The disruptive effects on the economy are exacerbated for countries without carbon tax or with a high exposure to natural disasters. In general, results support the need for a uniform policy mix to counteract climate change with a balance between demand-pull and technology-push policies.
Keywords: C11; C33; E32; E58; Q5; 330; Environmental policy; Environment-related technologies; Physicalrisks; Business cycle; SVAR